Christianity and the Nuclear Issue - Tamney, Joseph B. (Sociological analysis, 1985)
The paper reports a study of religion and attitudes concerning nuclear disarmament. It was expected that because of the recent pronouncements of Catholic leaders, Catholics would favor a freeze more than Protestants. Data were collected from a sample of respondents living in the Murine, Indiana SMSA (“Middletown”; N=393). It was found that Catholics more than Protestants and those aware that their church leaders have supported a freeze were more likely to favor a freeze. Controlling for nonreligious variables did not change these results.